Pengaruh Pendidikan Kesehatan tentang Senam Disminore terhadap Pengetahuan Remaja Putri di SMP Negeri 11 Kota Jambi - Kamala Syartina; Dwi Kartika Pebrianti; Ariyanto Ariyanto; Yuliana Yuliana; Marnila Yesni; Rahmi Dwi Yanti (Universitas Baiturrahim, 2023)
Based on the prevalence of dysmenorrhea in teenagers in Indonesia was noted at around 64.25%. As a result, it can interfere with daily activities such as school, impaired motivation and concentration in learning. It is overcoming dysmenorrhea through dysmenorrhea exercises, namely relaxation used to reduce pain. This study aims to determine the effect of health education on young women's knowledge of Disminore Gymnastics at SMP N 11 Jambi City. This research is a quantitative, pre-experimental research design. The method used is a one-group pretest-posttest design. The population is 107 respondents, and the sample uses Simple Random Sampling of as many as 20 respondents. The instruments in the questionnaire form use univariate and bivariate data analysis (T-test). This research was conducted in October 2022-July 2023. This study shows that the average value of respondents' knowledge before being given health education was 6.20%, while the knowledge of respondents after being given health education increased by 11.10%. The results of the paired-test statistical test obtained a p-value of 0.000 <0.05, meaning that there was an effect of health education about dysmenorrhea exercise on young women's knowledge. It can be used as input for SMP Negeri 11 Jambi City to increase youth knowledge about monthly dysmenorrhea exercises to reduce menstrual pain. Keywords: dysmenorrhea, gymnastics, health education, knowledge